Pengaruh Kemudahan, Manfaat Dan Pengetahuan Terhadap Minat Penggunaan E-Commerce Pada Generasi Z - Mahfiyah Mahfiyah; Muthmainnah Muthmainnah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
Abstract This study aims to determine the effect of convenience, benefits and knowledge on the interest in using e-commerce in generation Z. The method in this study uses descriptive quantitative methods. Data was taken by distributing the questionnaire link to Generation Z in Jember Regency as many as 138 people. Data were analyzed using the SPSS 2019 application with multiple linear regression analysis. The results of the analysis show that partially: Ease of Use has a significant positive effect on interest in using e-commerce in Generation Z. Usefulness/Benefits have a significant positive effect on interest in using e-commerce in Generation Z. Knowledge has a significant positive effect on interest in using e-commerce commerce in Generation Z. Simultaneously convenience, benefits and knowledge have a significant effect on the interest in using e-commerce in generation Z.